Polytechnic Students' Preferences in Choosing the Reading Materials for English Language Classroom - Santhy Subbarau; Marissa Bt. Abd. Mustafa (IJLECR (International Journal of Language Education and Cultural Review), 2016)
Reading has been a core of language learning skills and an essential tool for lifelong learning for centuries. Malaysian's language classroom scenario looks upon reading as a toughest task amongst the students in comprehending English texts. Facts were found referring to reading and the selection of materials correlates in bringing the best in comprehending what has been read. In Polytechnic System, language learning in diploma courses is compulsory. In an absolute condition, it's to highlight on the selection of reading materials on what do students seek and preferred. Students want variety and look into many modes for aspiration as a guide and input for the language learning classroom. This study aims to identify the polytechnic students' preferences towards reading materials and to find out the factors that influence the polytechnic students' choice of reading materials. Samples of respondents are from Polytechnic Banting Selangor (PBS), the diploma students in Mechanical and Aircraft Maintenance Engineering department.